Impact of Stubble Heights on Native Hay Meadows in Southeast Kansas - Junior I. Yasuoka; Wendie Powell; Walter H. Fick; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
Management practices affect hay production in native meadows. The objective of this study was to evaluate how stubble heights affect forage yield and quality in a native meadow. Prescribed spring burns contribute to improving forage quality. Setting the stubble height at 3 inches resulted in high forage quality and had a low yield impact.
Keywords: biomass; management; hay production; residue